Victorian Eco-Spiritualism: Environmental Citizenship and the Occult Revival in Nineteenth-Century Women’s Writing - Contreras Ameduri, Clara (International Journal of English Studies, 2024)
The purpose of this article is to explore the notion of environmental citizenship in the work of nineteenth-century spiritualist women. By examining female occultist participation in vegetarianism, anti-vivisection, and anti-industrial communalism, it is possible to observe an eco-spiritualist line in women’s writing, one which facilitated a more holistic and respectful approach to non-human subjectivities. Such texts therefore offer useful evidence of how spiritualist beliefs allowed women to influence public policies regarding the human-nature relationship in the long nineteenth century.